Philanthropic activities by Japanese companies in Thailand in the era of CSR : a cale study of the Redemptorist Vocational School and Panasonic Thailand - Sawauchi, Ayako (Chulalongkorn University, 2013)
Thesis (M.A.)--Chulalongkorn University, 2009